2019
DOI: 10.1007/s11423-019-09658-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting struggling readers with digital game-based learning

Abstract: This study investigates the effectiveness of a digital game-GraphoLearn (GL)-in supporting second-grade students who have persistent difficulties with acquiring accurate and fluent reading skills. The participants (N = 37) were randomly assigned either to a 6-week intervention including sessions with GL, in addition to school-provided support, or a control group receiving only school-provided support. The intervention took place at the students' homes and schools under the supervision of their parents and teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 50 publications
2
44
1
3
Order By: Relevance
“…We tested models with mean response time and response accuracy as mediators, but our hypothesis was not supported. Among GL Reading players, the correlations suggested that self-efficacy was marginally associated with faster response times, and faster response times were related to improvement in word reading fluency, which is consistent with an earlier GL study, which suggested that game performance is a mediator between child's cognitive engagement in gameplay and learning gains (Ronimus et al, 2019). However, the indirect effects from self-efficacy via game performance to learning gains were not significant, which could be because of lack of statistical power caused by small sample size.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We tested models with mean response time and response accuracy as mediators, but our hypothesis was not supported. Among GL Reading players, the correlations suggested that self-efficacy was marginally associated with faster response times, and faster response times were related to improvement in word reading fluency, which is consistent with an earlier GL study, which suggested that game performance is a mediator between child's cognitive engagement in gameplay and learning gains (Ronimus et al, 2019). However, the indirect effects from self-efficacy via game performance to learning gains were not significant, which could be because of lack of statistical power caused by small sample size.…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, previous studies have not addressed the role of self-efficacy in children's game-based learning of literacy skills. However, previous studies concerning self-regulation and engagement (Kegel et al, 2009;Kegel & Bus, 2012;Ronimus et al, 2019;van de Sande et al, 2016) suggest that factors related to persistence and effort may be important in this kind of training. We also aim to identify potential mediators between self-efficacy and learning by utilising the game log data, namely information about response times and response accuracy.…”
Section: Present Studymentioning
confidence: 92%
See 1 more Smart Citation
“…We reviewed the method section in each paper to confirm the word "traditional" reflected an instructional treatment that researchers were comparing to a competing instructional treatment. The articles that met this criterion were Mavridis, Katmada, and Tsiatsos 2017 2018, and Rominus, Eklund, Pesu, and Lyytinen (2019). None of these research articles include references linking their designs and conclusions with an instructional theory framework (Situation, Conditions, Values, and Methods) such as the one described above or any type of design theory (Reigeluth & Carr-Chellman, 2009a) that "…identifies good methods for accomplishing goals (p. 7) 4 .…”
Section: The Instructional Theory Framework Is Lostmentioning
confidence: 99%
“…Recent GL studies reveal that severe dyslexia is very difficult to overcome when intervention is started after the child has been affected by the related failures during the first semester (Ronimus et al, 2019 ). Thus, the optimal starting time is when children enter school.…”
Section: Introductionmentioning
confidence: 99%